Features of drug addiction treatment programs in Atlantic Canada that help (or not) with access and retention: A qualitative study. - Holly Mathias; Lois A Jackson; Jane A Buxton; Anik Dubé; Niki Kiepek; Jo-Ann MacDonald; Fiona Martin; Jen Smith (PLoS ONE)
Access to government-funded addiction treatment programs can reduce harms experienced by people who use substances (PWUS). There is some research on what features (e.g., policies and practices) of treatment programs help or do not help with access; however, not much is known about program directors' and physicians' perspectives of these features in Atlantic Canada. One-on-one semi-structured qualitative interviews were conducted with program directors and physicians working in government-funded addiction treatment programs in Atlantic Canada in 2021. Interview questions focused on perspectives of program features that helped or not with access and retention, including perspectives on changes due to COVID-19. Data were coded and analyzed using grounded theory techniques to develop themes and subthemes. Fourteen individuals were interviewed. They identified several features that helped (e.g., quick access) or did not help (e.g., wait times) with access and retention. Participants shared some features that changed due to COVID-19, including some that helped (e.g., virtual services) and did not (e.g., limited program spaces). Participants suggested changes that could support access and retention, including better linkages to mental health supports. This paper highlights program directors' and physicians' perspectives on how program features inform access and retention in Atlantic Canada. Findings on changes made during COVID-19 point to the need to maintain the changes that were helpful and implement additional changes to better support access for more PWUS. To support the implementation and sustainability of these changes, more resources must be invested.